Development and instructional application of u-library on butterfly and wetland ecology for context-aware ubiquitous learning. (7th June 2010) - Shih, Ju-Ling; Hwang, Gwo-Jen; Chu, Yu-Chung
The aim of this research is to build a digital library for mobile and ubiquitous learning situation. To facilitate the concept of context-aware ubiquitous learning, the database includes not only the metadata of digital content but also the global positioning system (GPS) waypoint and radio frequency identification (RFID) positioning codes with the instructional application on butterfly and wetland ecology content. The evaluation of the u-library system was done with questionnaire that contains three parts, namely website design, system uniqueness and potential to instruction. The results find that u-library system has gained users' positive responses in all aspects. The feature of containing GPS waypoint has made the u-library particularly unique and different from other systems.